Penerapan Pendekatan Pembelajaran Inkuiri Terstruktur Untuk Meningkatkan Kompetensi Keterampilan Koneksi Matematis, Memecahkan Masalah, dan Komunikasi Matematis - Niko Sudibjo; Maria Magdalena Isti Handayani (JTP - Jurnal Teknologi Pendidikan, 2017)
The aim of the research is to analyze the improvement of mathematical connection, problem solving, and mathematical communication skills by implementing structured inquiry-based learning. The questions to be answered are how the process of applying structured inquiry-based learning to improve the competence of mathematical connection, problem solving, and mathematical communication skills in the topic of Multiplication of grade I SD. Royal Tunas Mulia; how the development of mathematical connection, problem solving, and mathematical communication skills of students with the application of structured inquiry-based learning; what obstacles are found and how to overcome them.This study employed a Classroom Action Research carried out in three cycles. The subjects were 20 Grade 1 students of SD. Royal Tunas Mulia. The data was gathered by using observation, field notes, written tests, documentation and it was analyzed using qualitative descriptive and quantitative methods. The results showed that structured inquiry-based learning improves on the students’ mathematical connection, problem solving, and mathematical connection.